2019
DOI: 10.1209/0295-5075/124/64003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-Langmuir adsorption on spreading in porous media

Abstract: When given solutes are transported in porous media flows, various propagation regimes can be observed depending on the adsorption isotherms. We perform numerical simulations to investigate the influence of an anti-Langmuir adsorption isotherm (overloading isotherm) on the spreading of a miscible solute-rich slice in a porous medium. Selecting the characteristic scaling of the solute concentration appropriately, the dynamics of the anti-Langmuir adsorbed solute is studied in the pure diffusion-convection condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…If the carrier fluid has a different viscosity than the sample solvent, VF can appear, which is dramatic for the efficiency of separation (Dickson et al (1997), Broyles et al (1998), De Wit et al (2005), Rousseaux et al (2007Rousseaux et al ( , 2011). In this context, it has been shown that adsorption on the porous matrix of components controling the viscosity of the fluids can influence the instability (Mishra et al (2007), Rana et al (2014Rana et al ( , 2018). As an example, the onset time of the instability can, in some cases, depend nonmonotonically on the retention parameter of the solute adsorption (Hota et al (2015)).…”
Section: Viscous Fingering In Reactive Systemsmentioning
confidence: 99%
“…If the carrier fluid has a different viscosity than the sample solvent, VF can appear, which is dramatic for the efficiency of separation (Dickson et al (1997), Broyles et al (1998), De Wit et al (2005), Rousseaux et al (2007Rousseaux et al ( , 2011). In this context, it has been shown that adsorption on the porous matrix of components controling the viscosity of the fluids can influence the instability (Mishra et al (2007), Rana et al (2014Rana et al ( , 2018). As an example, the onset time of the instability can, in some cases, depend nonmonotonically on the retention parameter of the solute adsorption (Hota et al (2015)).…”
Section: Viscous Fingering In Reactive Systemsmentioning
confidence: 99%
“…The peak profiles for L and AL displacements at time t ¼ 3 Â 10 4 are shown in the inset of Fig. 4(b) (Rana et al, 2019). It is seen that the L-AL alternation gives a smaller mixing length at a given time than both pure L or AL systems, thanks to this accordion effect.…”
Section: Accordion Effect and Reduction Of Peak Wideningmentioning
confidence: 92%
“…This isotherm is valid provided c m < c th ¼ 1=b AL where c th corresponds to the threshold concentration of the column. Because of the increased adsorption at larger c m , the velocity of the solute in the mobile phase is smaller in the zones of larger concentrations, which results in the formation of a SL at the rear interface and of a RF wave at the frontal interface (Lin et al, 1995;Rana et al, 2019). Anti-Langmuir isotherms feature therefore asymptotic triangular peaks with a SL at the back (see Fig.…”
Section: Anti-langmuir Isothermmentioning
confidence: 99%
“…In contrast, according to our statistical thermodynamic framework, Type III differs from Types I and II only by the sign of B ; deriving a separate isotherm model applicable only to Type III, such as the anti-Langmuir model, , has been made redundant. (Note that the anti-Langmuir model corresponds to B > 0 and C = 0.)…”
Section: Theorymentioning
confidence: 99%